Review of Different Methods for Siting and Sizing Distributed Generator - Somefun, Tobiloba; Popoola, Olawale; Abdulkareem, Ademola; Awelewa, Ayokunle (International Journal of Energy Economics and Policy, 2022)
Distributed generator has been confirmed to be a means by which installation of a new centralized generator can be delayed or postponed in the era of deregulation. It helps to minimize line losses and improve voltage profile. the benefits associated with distributed generator can be greatly harnessed when DG is optimally sited and sized within power system network. In this study, different methods used by previous researchers were extensively reviewed. The summary of the methodologies from previous works were itemized one after the other. This was done under the impact of distributed generator in a network. These methodologies are summaries under three categories namely; analytical, meta-heuristic and hybrid optimization methods. All the methods are based on solving non-linear load flow solution except the Inherent Structural Network Topology. In this review work, the inherent structural network topology is recommended for further studies to solve power system problems.